An ectopic pregnancy under the liver. (29th September 2010) - Nielsen, Kamilla Gerhard; Pedersen, Anette Tønnes
Abstract : Ectopic pregnancy is a common but potential life-threatening condition. The most common ectopic location is in the fallopian tube. Here we report a case of an ectopic pregnancy in a non-communicating fallopian tube placed under the liver.